Numerical modelling of chromatic effects on axicon-focused beams used to generate HOFI plasma channels. (July 2020) - Ross, A J; Alejo, A; von Boetticher, A; Cowley, J; Holloway, J; Jonnerby, J; Picksley, A; Walczak, R; Hooker, S M
Abstract: Hydrodynamic optical-field-ionised (HOFI) plasma channels promise a route towards high repetition-rate, metre-scale stages for future laser plasma accelerators. These channels are formed by hydrodynamic expansion of a plasma column produced by optical field ionisation at the focus of a laser, typically from an axicon lens. Since the laser pulses used to generate the initial plasma column are of sub-picosecond duration, chromatic effects in the axicon lens could be important. In this paper we assess these effects using a numerical propagation code. The code is validated using analytical formulae and experimental data. For the parameter range investigated, dispersive effects are found to be of minor importance, reducing the peak on-axis intensity in the focal region by approximately 10%.